Dementia secondary to a potentially treatable cause - role of GPs - Rathor, Mohammad Yousuf; Wai, Kyaw Tun; Abdul Rashid, Mohd Amran; Akter, Seikh Farid Uddin (2009)
Dementia is tragic mind-wrecking disease, defined as a multifaceted decline in cognitive function severe enough to interfere with activities of daily life. We present herein two patients who presented with loss of memory and altered behaviour. The purpose of these case reports is to alert the health professionals, especially general practitioners, in detection of “potentially treatable " cases of dementia that can be treated effectively to restore normal or nearly normal intellectual function.